2020
DOI: 10.1186/s12913-020-05685-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of pharmacy workers on antihypertensive and anticonvulsant drugs for managing pre-eclampsia and eclampsia in Bangladesh

Abstract: Background Pharmacy workers in Bangladesh play an important role in managing pregnancy complications by dispensing, counselling and selling drugs to pregnant women and their families. This study examined pharmacy workers’ drug knowledge and practice for pre-eclampsia and eclampsia (PE/E) management, including antihypertensives and anticonvulsants, and determine factors associated with their knowledge. Methods A cross-sectional survey with 382 pharmacy workers in public facilities (government) and private pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…This study has demonstrated that the trained Grade C pharmacists had better knowledge about good pharmacy practices including counseling the customers, which is similar to the findings in Tanzania that has demonstrated that trained drug dispensers had better knowledge on antimicrobial resistance (AMR) and were better aware about giving instruction while dispensing medicine to customers ( Valimba et al, 2014 ). Our study findings also support a previous evidence in Bangladesh documenting that trained drug dispensers were likely to have correct knowledge on anti-hypertensive and anticonvulsant drugs than those who had no training ( Valimba et al, 2014 ; Roy et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…This study has demonstrated that the trained Grade C pharmacists had better knowledge about good pharmacy practices including counseling the customers, which is similar to the findings in Tanzania that has demonstrated that trained drug dispensers had better knowledge on antimicrobial resistance (AMR) and were better aware about giving instruction while dispensing medicine to customers ( Valimba et al, 2014 ). Our study findings also support a previous evidence in Bangladesh documenting that trained drug dispensers were likely to have correct knowledge on anti-hypertensive and anticonvulsant drugs than those who had no training ( Valimba et al, 2014 ; Roy et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The hospital faculty/department of pharmacy is a specialized department, typically under the direct management of the hospital director, who is responsible for the management of all hospital pharmacists and pharmacy-related workload [2,3]. The work of a hospital-pharmacist includes, but not limited to, planning for drug supply, providing drug information, administering and monitoring the import/dispensing/storage of drugs, implementing the activities of the drug and treatment council, performing clinical pharmacy consultations, monitoring drug usage, participating in pharmacovigilance, reporting information related to adverse drug effects, and conducting scientific research and training [2,4]. Due to the diversity of this workload, a hospital pharmacist has no easy time performing these tasks rapidly and efficiently, resulting in workload pressure, stress, depression, and reduced job satisfaction [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%